Doing More for Less? : New Evidence on Lobbying and Government Contracts - Agca, Senay (IMF Working Papers; Working Paper ;, 2019)
Why do firms lobby? This paper exploits the unanticipated sequestration of federal budget accounts in March 2013 that reduced the availability of government funds disbursed through procurement contracts to shed light on this question. Following this event, firms with little or no prior exposure to the federal accounts that experienced cuts reduced their lobbying spending. In contrast, firms with a high degree of exposure to the cuts maintained and even increased their lobbying spending. This suggests that, when the same number of contractors competed for a piece of a reduced pie, the more affected firms likely intensified their lobbying efforts to distinguish themselves from the others and improve their chances of procuring a larger share of the smaller overall. These findings are stronger in government-dependent sectors and when there is intense competition. The evidence is more consistent with a rent-seeking explanation for lobbying.